Standardizing Magnetic Resonance Imaging Protocols, Requisitions, and Reports in Multiple Sclerosis: An Update for Radiologist Based on 2017 Magnetic Resonance Imaging in Multiple Sclerosis and 2018 Consortium of Multiple Sclerosis Centers Consensus Guidelines. Issue 1 (January 2019) - Arevalo, Octavio; Riascos, Roy; Rabiei, Pejman; Kamali, Arash; Nelson, Flavia
Abstract : Abstract: The advent of magnetic resonance imaging has improved our understanding of the pathophysiology and natural course of multiple sclerosis (MS). The ability of magnetic resonance imaging to show the evolution of MS lesions on sequential scans has brought it to be one of the endpoints in clinical trials for disease-modifying therapies. Based on the most updated consensus guidelines from the American (Consortium of MS Centers) and European (Magnetic Resonance Imaging in MS) boards of experts in MS, this document shows the most relevant landmarks related to imaging findings, diagnostic criteria, indications to obtain a magnetic resonance, scan protocols and sequence options for patients with MS. Although incorporating the knowledge derived from the research arena into the daily clinical practice is always challenging, in this article, the authors provide useful recommendations to improve the information contained in the magnetic resonance report oriented to facilitate communication between radiologists and specialized medical teams involved in MS patients' multidisciplinary care.